An overview of the effect of stirrer design on the mechanical properties of Aluminium Alloy Matrix Composites fabricated by stir casting - Farooq Muhammad; Shawnam Jalal (Zanco Journal of Pure and Applied Sciences, 2022)
Aluminum Matrix Composites are widely utilized in a variety of applications, and their popularity is growing due to their excellent performance, low cost, and low environmental footprint. Metal Matrix Composites are made in a variety of ways, including liquid and solid states, but stir casting is the most common because of its flexibility, inexpensiveness, and offering a diverse range of materials and manufacturing conditions. The key challenge in the procedure is the homogeneous dispersion of reinforcing particles. The homogeneous dispersion of particles inside the metal matrix determines the microstructure and mechanical properties of the composites. Stirrer design has a vital role and it can be more effective through optimizing it. All available literature was reviewed from 1968 which stir casting method was initiated to produce Aluminium matrix composites. Mixer designs and mixing efficiency were also investigated in other related studies. The scope of this paper explores the experimental contributions of stirrer design in the production of composites. There are many variables in stir casting The large number and overlap of parameters appear to have an impact on the uniform distribution of reinforcing particles. Researchers on their path to the appropriate technique have had promising results with only their circumstances, without being able to generalize their findings. In this article, previous findings and contributions have been collected, organized, compared, and presented. Finally, several conclusions have been raised and scopes for the new research have been identified.